Bromelicolous Polypedilum Kieffer from South Brazil (Diptera: Chironomidae) - Pinho, Luiz Carlos; Mendes, Humberto Fonseca; Andersen, Trond; Marcondes, Carlos Brisola (Zootaxa, 2013)
Polypedilum (s. str.) kaingangi sp. n. is described and figured as male, female, pupa and larva and the female and immature stages of Polypedilum (s. str.) solimoes Bidawid-Kafka, 1996 are described and illustrated. The immatures of both species inhabit leaf axils of various bromeliad species in the Atlantic rainforest in Santa Catarina State, South Brazil.